Pilgrims, Pickers and Honky-Tonk Heroes: My Personal Time with Music City Friends and Legends in Rock 'n' Roll, R&B, and a Whole Lot of Country - Ghianni, Tim (Rowman & Littlefield Publishers, 2023)
He didn’t know it at the time, but Tim Ghianni’s love affair with Nashville and its musical artists began on a steamy night in 1972, when the twenty-year-old author had unsolicited help from honky-tonkin’ legends Bobby Bare and Shel Silverstein during an after-midnight “salvation” of the city. It was the beginning of a lifelong urban romance that Ghianni would pursue during a career as a journalist in Middle Tennessee, interviewing Nashville’s biggest stars and developing friendships with musicians of all kinds. With a preface by Bobby Bare and a foreword by Peter Cooper, Pilgrims, Pickers and Honky-Tonk Heroes is Tim Ghianni’s love letter and nostalgic swan song, recounting the storied musical history of Nashville as well as the dramatic changes the city has seen over the course of fifty years. The Nashville of today—with one hundred newcomers a day from places like Los Angeles and New York and fresh waves of musicians making up a new modern soundtrack—is not the same city he made his home in 1972, for better and for worse. Time changes everything, even a beloved American city, but this briskly told and warmly remembered book recounts the countless friends, adventures, and anecdotes that capture the essence of Music City across a half-century.